Research on Crowbar Protection Circuit in Traction Converter - Yupeng LI; Jianhui FU; Yongjiang LIU; Ronghui FAN; Xionghui TANG; Zhenjun LIN (机车电传动)
In view of the current status of IGBT failures causing serious consequences in traction converter, several common IGBT power module failure modes were analyzed, crowbar protection circuit and principle were introduced, and the qualitative and quantitative comparisons of with/without crowbar protection circuit in various failure modes were carried out with circuit analysis and energy density simulation. Finally, the effectiveness of crowbar protection circuit in preventing the single-device short circuit then causing bridge-through faults, reducing module damage, and preventing device damage due to the single-device short circuit failure was verified by multiple tests.